Prispevek k določevanju porekla sladkorja v vinih Republike Slovenije s pomočjo nuklearne magnetne resonance (NMR) : doktorska disertacija - Kocjančič, Mitja (M. Kocjančič, 1995)
Summary: Enrichment of grape must and young wine with sugar in order to rise the natural alcohol content in wine is allowed in all countries of the European Union (EU) only under certain conditions. Slovene "Law on wine and other products from grape and wine" (Official Gazette of the Republic Slovenia, No. 16/74) also forbids the correction of must and grapes by adding sugar, concentrated must, other sugar substances and acids. Exceptionally, the enrichment with sugar or concentrated must is allowed if, due to the consequences of unfavourable weather conditions or diseases felt on vine, less sugar is recorded in grapes, must or grape pulp than the normal quantity allowed for certain grape variety grown in certain vine growing district.